The Electric Shock during Acupuncture: A Normal Needling Sensation or a Warning Sign - Yongsong Guo; Ke Zhu; Jing Guo; Yongbing Kuang; Zhihui Zhao; Weihong Li (Neural Plasticity)
The electric shock has been proposed as one of the new needling sensations in recent years. In acupuncture sensation scales, the electric shock is included by ASS and SNQS, but not SASS, MASS, and C-MMASS. Some scholars argue that the electric shock is a normal needling sensation, but some researchers do not agree with this view. This problem has not been resolved due to a lack of evidence from basic research. Literature and research point out that the electric shock is caused by inserting a needle into the nerve directly. A question of considerable scientific and practical interest is whether the electric shock should be a normal needling sensation. In this article, we review the historical documentation of the needling sensation and the process of formulating and improving acupuncture sensation scales to suggest that the electric shock may not be a normal needling sensation. Secondly, we collected and analyzed cases of nerve injury caused by acupuncture accompanied by the electric shock and why acupuncture caused the electric shock without nerve injury. It suggests that there may be a correlation between the electric shock and peripheral nerve injury, and acupuncture manipulation is an essential factor in adverse acupuncture events. Finally, we put forward that the electric shock during acupuncture is a warning sign that the peripheral nerve may be injured, rather than a normal needling sensation. In the future, we hope to have experimental studies on the mechanism of the electric shock or observational studies on the correlation between the electric shock and peripheral nerve injury to verify.